2000
DOI: 10.1021/jf000528n
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of a Monoclonal Antibody against the β-Adrenergic Agonist Ractopamine

Abstract: A monoclonal antibody was generated toward the beta-adrenergic agonist ractopamine hydrochloride ¿(1R,3R),(1R, 3S)-4-hydroxy-alpha-[[[3-(4-hydroxyphenyl)-1-methylpropyl]amino]methy l]benzenemethanol hydrochloride¿. Ractopamine-glutarate-keyhole limpet hemocyanin (KLH) was used as the antigen for antibody generation in mice. Clone 5G10, secreted antibody with isotype IgG1kappa, was used for the development of an immunoassay. The selected antibody was specific for racemic ractopamine with an IC(50) of 2.69 +/- 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…During the experimental process, the choice of the suitable carriers, particularly the immunogen carrier was very important. [29][30][31][32] The physico-chemical property of BSA is stable, not changing, and facilitating the chemical treatments, and it can keep high solubility at different pH and ionic strength. 33 As a carrier protein, the pro-source relations between BSA and OVA is distant, with a low level of cross-reactivity, OVA as the carrier protein was chosen, so it was easy to remove the antibodies to the carrier protein BSA, and greatly reduce the labor intensity of the test.…”
Section: Discussionmentioning
confidence: 99%
“…During the experimental process, the choice of the suitable carriers, particularly the immunogen carrier was very important. [29][30][31][32] The physico-chemical property of BSA is stable, not changing, and facilitating the chemical treatments, and it can keep high solubility at different pH and ionic strength. 33 As a carrier protein, the pro-source relations between BSA and OVA is distant, with a low level of cross-reactivity, OVA as the carrier protein was chosen, so it was easy to remove the antibodies to the carrier protein BSA, and greatly reduce the labor intensity of the test.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of studies, it has been found that some viral transfer gene expression products have tyrosine kinase (PTK) activity [1]. Therefore, PTK has become an important breakthrough in studying the mechanism of oncogenes and exploring the treatment of tumor diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of hapten partly determines the affinity and specificity of antibody, then performance of immunoassay. Up to now, few attempt has been made to prepare hapten of RAC in the literatures (Haasnoot et al, 1994;Shelver, Smith, & Berry, 2000). The aim of the study was to synthesize new RAC haptens in order to produce polyclonal antibody with high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%